Konvencija za pripravo osnutka statuta Dežele Furlanije Julijske krajine in slovenska manjšina - Brezigar, Bojan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
The recent constitutional reforms in Italy obligate the Friuli-Venezia Giulia region to prepare a draft of the new statute which will have to be ratified by the State Parliament. In accordance with a special procedure, a special Convention was formed, its members being - apart from the Assembly represenatives - local administration officials and representatives of trade unions and linguistic minorities. The article discusses the procedure of the draft statute formation with special emphasis on the issues concerning the Slovene minority in Friuli-Venezia Giulia. It brings an analysis of the Convention's activities and the formation of the concluding document, while a special supplement contains the proposals submitted by the Slovene minority in Italy and the text, sent by the regional assembly to the Parliament. Comparison shows that most of the Slovene minority's proposals were incorporated into the final version. The author was himself a member of the Convention, although the text is based solely on the available written sources.
Keywords: Italija; Italy; Friuli–Venezia Giulia; Furlanija-Julijska krajina; statut; narodne manjšine; zaščita manjšin; Slovenci; Slovenes